PENGARUH STRUKTUR MODAL, RISIKO KREDIT DAN DANA PIHAK KETIGA TERHADAP KINERJA KEUANGAN PERBANKAN - Setia Devi, Anak Agung Istri; Dewi, Putu Pande R. Aprilyani; Kusuma, Putu Sri Arta Jaya; Arlita, I G.A. Desy (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyse the effect of capital structure, credit risk, and third-party funds on banks' financial performance, taking into account the challenges magnified by the COVID-19 pandemic. The global economic shock caused by the pandemic increased pressure on banks' capitalisation due to the decline in economic activity. At the same time, credit risk surged as many businesses and individuals faced financial difficulties leading to an increase in bad debts. In addition, economic uncertainty encouraged customers to withdraw or hold deposits, creating pressure on bank liquidity. This study uses secondary data from the annual financial statements of 97 banking companies for the period 2021-2023. The analysis technique used is multiple linear regression to test the relationship between these variables. The results showed that capital structure has a positive and significant effect on financial performance. Credit risk was also found to have a positive and significant effect on financial performance. Similarly, third party funds made a significant positive contribution. These findings provide an in-depth understanding of the importance of managing financial elements in maintaining banking stability and performance, especially in the midst of unpredictable economic challenges